Geometry of Khalakan Anticline, Northeastern Iraq - Manal Shakir Al-Kubaisi; Ayyed Hussein Ward (Tikrit Journal of Pure Science)
This research deals with the geometry of Khalakan Anticline by using field data. The anticline is located in NE Iraq, within the High Folded Zone of the Iraqi Western Zagros Fold – Thrust Belt where the southwestern limb of it represents the boundary between the Low  and High folded zones. The age of the exposed rocks in the study area ranges from Cretaceous to Late Pliocene. Qamchuqa and Kometan formations expose in the two limbs as oldest rocks, while the youngest rocks in the northeastern limb are covered by Dokan Conglomerate. Consequently the fold geometry was determined by the measured field data of Qamchuqa and Kometan formations only. Khalakan anticline was described as asymmetrical and overturned fold, with northeastern vergency, where the mean attitude of the NE limb is 220 ᴏ/89 ᴏ and the mean attitude of the SW limb is 219 ᴏ/55° in terms of dip direction and dip amount. The attitude the fold axis in terms of trend and plunge is 130°/1°, the attitude of the axial plane is 220°/72° in terms of dip direction and dip amount, the interlimb angle is 34°, consequently the fold was classified as Close Fold.